Transferring two names of Chlamydogramme to Tectaria (Pteridophyta: Tectariaceae) - Zhang, Xin; Zhang, Liang; Zhang, Li-Bing (Phytotaxa, 2019)
Following recent taxonomic treatment we here transfer two species of ferns from Chlamydogramme to Tectaria (Tectariaceae). We also lectotypify Gymnopteris hollrungii Kuhn.